Answer: s - r
==================================================
Step-by-step explanation:
We'll need these trig ratios
- sine = opposite/hypotenuse
- cosine = adjacent/hypotenuse
Refer to the diagram below.
sin(B) = r = r/1 which tells us that the side opposite angle B is r units long. The hypotenuse is 1.
cos(B) = s = s/1 means the adjacent side to angle B is of length s
sides r and s are the two legs of the right triangle.
----------
From that diagram, we can then say:
sin(angle) = opposite/hypotenuse
sin(C) = s/1
sin(C) = s
This is identical to cos(B). We can say cos(B) = sin(C)
Also, we can say:
cos(angle) = adjacent/hypotenuse
cos(C) = r/1
cos(C) = r
So cos(C) = sin(B)
This works because B+C = 90
----------
So,
sin(C) - cos(C) = cos(B) - sin(B) = s - r